2007
DOI: 10.1159/000103174
|View full text |Cite
|
Sign up to set email alerts
|

A functional genomics approach to the study of avian innate immunity

Abstract: A second-generation 4,959 element cDNA microarray has been created and evaluated for its potential use in examining the avian innate immune response. The elements in this array were obtained from EST libraries of stimulated avian PMNC-derived monocytes/macrophages and supplemented by genes of interest from several specific innate immune pathways. The elements are spotted in triplicate resulting in 14,877 total spots per slide. The avian innate immunity microarray (AIIM) contains 25 avian interleukin, chemokine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 49 publications
(23 reference statements)
0
10
0
Order By: Relevance
“…On the one hand, H3N2 influenza virus could cause the up-regulation of MHC class I mRNA expression levels [39]. On the other hand, the expression of MHC class I did not increase due to the infection of macrophages with a low pathogenic H7N2 AIV [40]. Thus, it can be suggested that H1N1 SwIV may be unable to inhibit MHC genes expression, which should be an important host factor for easily controlling virus.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, H3N2 influenza virus could cause the up-regulation of MHC class I mRNA expression levels [39]. On the other hand, the expression of MHC class I did not increase due to the infection of macrophages with a low pathogenic H7N2 AIV [40]. Thus, it can be suggested that H1N1 SwIV may be unable to inhibit MHC genes expression, which should be an important host factor for easily controlling virus.…”
Section: Discussionmentioning
confidence: 99%
“…The development of microarrays, pyrosequencing technology, and next-generation massively parallel sequencing methods has introduced high-throughput means of discovering genes and gene networks underlying host and parasite traits and interactions (Hill et al 2005;Keeler et al 2007;Baton et al 2008). These technologies have enabled the field to move from the previously described steps of inferring gene involvement through phylogenetic relationships or associating quantitative traits with genetic regions to directly measuring transcriptional changes in potentially hundreds of different genes during the production of a particular phenotype.…”
Section: Methods Of Gene Discovery: Gene Expressionmentioning
confidence: 99%
“…No statistical difference was found in the transcript levels of IL-6, IL-8, or of CXCL1 and CXCL2 mRNA transcripts. Bacterial pathogenassociated molecular patterns (PAMPs) recognized by pathogen recognition receptors (PRRs), which are expressed by intestinal epithelial cells, result in cytokine gene transcription (IL-1β, IL-6, IL-8 and chemokynes) from the innate immune repertoire (Keeler et al, 2007;Wigley, 2013). Interestingly, disrupted or live C. jejuni bacteria have been shown to have different effects on the activation of the PRRs signalizing pathways (AlSayeqh et al, 2010;De Zoete et al, 2010).…”
Section: Campylobacter Jejuni Increases Transcribed Il-1β and Causes mentioning
confidence: 99%